Nigeria’s Foreign Policy and Economic Relations with International Economic Organizations in the Fourth Republic: A General Appraisal - Saleh, Bailey (Kashere Journal of Politics and International Relations, 2023)
In spite of the fact that Nigeria has had active economic interactions with international economic organizations through its foreign policy in the fourth republic, the benefit/rewards derivable from such engagements are not commensurate with the efforts made in line with the interdependence theory or even the hegemony theory. However, the country’s engagement with the World Bank and to some extent the EU in the Fourth Republic can generally be regarded as very rewarding (beneficial). Foreign capital inflows through Foreign Direct Investment, Foreign Portfolio Investment, foreign goodwill, home remittances, and financial assistance in forms of credits and loans have been granted to Nigeria to assist the country in general infrastructural development and to generally grow the domestic economy between 1999 and 2022. The failure of the country to direct all these foreign capital inflows towards boosting the industrial, manufacturing and other non-oil exports informed the need for this study. The study is a qualitative one where data was generated through secondary sources such as books, journals, magazines, online sources, newspapers and periodicals. The data generated was analyzed through descriptive method.